Arterial Stiffness in a Rural Population of Argentina: Pilot Study - Diaz, Alejandro (2015)
Introduction: Aortic stiffness evaluated through pulse wave velocity (PWV) measurement is nowadays accepted as a reliable parameter to estimate cardiovascular risk. However the data about arterial stiffness in South America come from urban populations. Aims: To determine the relationship between PWV changes and ageing and to identify the rate of change in each decade of life. Methods: PWV was measured in the carotid-femoral pathway in 400 inhabitants of Vela town and clinical parameters were recorded. Results: The prevalence of hypertension, dyslipidemia and diabetes was 33.5, 17.5, 5 % respectively. PWV was positively correlated with age (r: 0.817, p = 0.01) and was greater after the fifth decade of life (9.72 ± 2.2 vs. 5.87 ± 1.55 m/s; p: 0.001) than in youngers than 50 years, respectively. The risk (odds ratio) of having PWV >10 m/s was higher in hypertensives (OR: 50, p = 0.001), older than 50 years (OR: 44, p = 0.001), diabetics (OR 9.5, p = 0.001) and dyslipidemic patients (OR: 5, p = 0.001). Conclusions: This is the first study in a rural population of Argentina which determines the relationship of PWV with age and cardiovascular risk. PWV shows a slower growth in subjects less than 50 years compared to older adults with a strong relationship to the process of arterial aging, the development of hypertension and cardiovascular risk.